Remembering the revolutionary past: the post-revolutionary generation(s) of Ethiopia and memory of the revolutionary period (late 1960s – late 1970s). Issue 2 (4th May 2021) - Ratner, David
ABSTRACT: The revolutionary period in Ethiopia (from the mid-1960s until the late 1970s) has long been a matter of scholarly interest and public debate. This article examines this period from the perspective of memory studies: the ways in which this period is remembered, the meanings attached to it and the roles the memory of this period plays in contemporary Ethiopian politics and society. More specifically, the paper focuses on perspectives of members of the post-revolutionary generation (i.e. Ethiopians in their 30s and 40s). As the study shows, members of this generation indeed see this period as extremely important both to them personally and to contemporary Ethiopia in general. It shows that the themes they associate with this period – the Leftist-Marxist ideology and practice, the legacy of armed struggle and violence, the ethnic/national question and more – are also issues crucial for understanding contemporary Ethiopia.